School Education in Manipur A Synoptic View - Singh, Thiyam Bharat (JOURNAL OF INDIAN EDUCATION, 2022)
The main objective of this present study is to examine school education and its associated multi-dimensional challenges of Manipur using selected educational indicators. The study finds that the State has performed well in terms of three educational parameters size, equity and efficiency. But Manipur still experiences higher dropout rates in its hill districts indicating an inequality of access to school education. Conflict and violence have impeded the progress of school education. Further, proxy-system of teachers, lack of trained teachers, lack of social support, lack of infrastructure, geographically isolated-schools, lackadaisical attitude, transport bottleneck, inappropriate curriculum, inappropriate pedagogy, political interference and poverty have exacerbated the problems. The study suggests three strategies: (i) a holistic approach to address the multidimensional socio-economic factors affecting school education, (ii) specific intervention for the geographically isolated schools in the hills and (iii) promoting equal access to school education.